Stress Corrosion Behavior of Ungrouted Pretensioned Concrete Beams - Velu Saraswathy; Han-Seung Lee; Subbiah Karthick; Seung-Jun Kwon (Advances in Materials Science and Engineering)
Prestressed concrete beams of size 150 × 150 × 1000 mm were designed, and two bonded cold-drawn 7 mm steel wires were stressed at 70% UTS under service conditions before concreting. The beams were cast with M40 grade concrete mix with various percentages of chlorides ranging from 0, 1, 2, and 3% by weight of cement and cured for 28 days. After 28 days, the stretching forces were released, the prestressing steel wire was allowed to regain its original length, the tensile stresses were transformed into a compressive stress in the concrete, and the stress corrosion behavior was assessed. Stress corrosion cracking (SCC) is due to the simultaneous action of stress, corrosive media, and material properties. The stress corrosion behavior of ungrouted pretensioned steel was assessed by using various electrochemical techniques such as electrochemical noise, open-circuit potential measurement, AC impedance, and potentiodynamic polarization measurements. The same experiments were conducted for rebars embedded in the concrete beam with various percentages of chlorides ranging from 0, 1, 2, and 3% by weight of chloride. After 30 days of exposure, the beams were tested for their flexural strength measurements to find out the load-bearing capacity.